Primary care provider perceptions of intake transition records and shared care with outpatient cardiac rehabilitation programs - Jamnik Veronica; Reid Robert D; Suskin Neville; Unsworth Karen; Yee Jonathan; Grace Sherry L (BMC, 2011)
Abstract Background While it is recommended that records are kept between primary care providers (PCPs) and specialists during patient transitions from hospital to community care, this communication is not currently standardized. We aimed to assess the transmission of cardiac rehabilitation (CR) program intake transition records to PCPs and to explore PCPs' needs in communication with CR programs and for intake transition record content. Method 144 PCPs of consenting enrollees from 8 regional and urban Ontario CR programs participated in this cross-sectional study. Intake transition records were tracked from the CR program to the PCP's office. Sixty-six PCPs participated in structured telephone interviews. Results Sixty-eight (47.6%) PCPs received a CR intake transition record. Fifty-eight (87.9%) PCPs desired intake transition records, with most wanting it transmitted via fax (n = 52, 78.8%). On a 5-point Likert scale, PCPs strongly agreed that the CR transition record met their needs for providing patient care (4.32 ± 0.61), with 48 (76.2%) reporting that it improved their management of patients' cardiac risk. PCPs rated the following elements as most important to include in an intake transition record: clinical status (4.67 ± 0.64), exercise test results (4.61 ± 0.52), and the proposed patient care plan (4.59 ± 0.71). Conclusions Less than half of intake transition records are reaching PCPs, revealing a large gap in continuity of patient care. PCP responses should be used to develop an evidence-based intake transition record, and procedures should be implemented to ensure high-quality transitional care.